Open active cloaking and illusion devices for the Laplace equation. (1st April 2016) - Ma, Qian; Yang, Fan; Jin, Tian Yu; Mei, Zhong Lei; Cui, Tie Jun
Abstract: We propose open active cloaking and illusion devices for the Laplace equation. Compared with the closed configurations of active cloaking and illusion devices, we focus on improving the distribution schemes for the controlled sources, which do not have to surround the protected object strictly. Instead, the controlled sources can be placed in several small discrete clusters, and produce the desired voltages along the controlled boundary, to actively hide or disguise the protected object. Numerical simulations are performed with satisfactory results, which are further validated by experimental measurements. The open cloaking and illusion devices have many advantages over the closed configurations in various potential applications.